‘Alaqat Dilaliyyah baina Alfaz al-Ruh wa al-Nafs wa al-Qalb fi al-Qur’an al-Karim - Ahmad Abdullah; Ulfah Luthfyatunnisa (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
This research aims to know the verses of using the terms spirit, soul, and heart in the Holy Quran, knowing its lexical and contextual meanings, knowing the relationship of its significance, and knowing the educational inclusion of its significance. This research is based on thinking that the words in the Qur'an have a semantic and contextual relationship and the educational inclusion of the meanings of the words soul, soul and heart in it depends on the science of Islamic education. As for the method used in this research, it is the method for analyzing the content with a semantic analysis, whereby the research is directed to analyzing the meanings of words. As for the entry in this research, it is the qualitative entry. By not researching the writer, we obtained the results from it. In the verses that contain the words of the soul, the soul, the heart and the like there are many, and each of its words has different meanings. The writers found the educational inclusion of the use of the words of soul, soul and title, which includes a method of Islamic education, which is the method of abandonment, sweetening, manifestation and the method of attachment, creation, verification, method of worship and the method of supplication, remembrance.